Economic Burden of Gastric Cancer: A Case of Iran. (13th March 2019) - Eghdami, Abed; Ostovar, Rahim; Jafari, Abdosaleh; Palmer, Andrew J.; Bordbar, Najmeh; Ravangard, Ramin
Purpose: Today, cancers have become a major cause of mortality in developed and developing countries. Among various cancers, gastric cancer imposes a huge economic burden on patients, their families, and on the health-care system. This study aimed to determine the economic burden of gastric cancer in Kohgiluyeh and Boyer Ahmad province of Iran in 2016. Methods: This was a cross-sectional cost of illness study conducted in Kohgiluyeh and Boyer Ahmad province of Iran in 2016, using a prevalence-based approach. All patients were studied using the census method (N = 110). The required data on direct medical, direct nonmedical, and indirect costs were collected using a data collection form from the patients' medical records, tariffs of diagnostic, and therapeutic services approved by the Ministry of Health and Medical Education in 2016. Results: The total cost and burden of gastric cancer in Kohgiluyeh and Boyer Ahmad province of Iran in 2016 were $US436 237, among which the majority were direct medical costs (59%). The highest costs among direct medical costs, direct nonmedical costs, and indirect costs were, respectively, related to the costs of medications used by the patients (35%), transportation (31%), and absence of patients' families from work and daily activities caused by patient care (56%). Conclusion: Our study has revealed for the first time high costs of gastric cancer in Iran. To decrease the total costs and burden, the following suggestions can be made: increasing insurance coverage and government subsidies for purchasing necessary medications, providing the required specialized care and services related to cancer diseases such as gastric cancer in other provincial cities rather than just in capital cities, and so on.